(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article analyzes the scholarly legacy of Imam Abu Hanifa (r.h.) in the field of Hadith studies based on classical sources. It highlights the position of hadiths narrated from Abu Hanifa (r.h.) within hadith collections and examines the significance of the works Musnad and Athar in the development of Hadith studies. The findings of the study demonstrate that Imam Abu Hanifa was not only a great jurist but also a recognized scholar in the science of Hadith.